2020
DOI: 10.1002/jor.24938
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hindfoot and ankle infections with Ilizarov external fixator or spacer, followed by secondary arthrodesis

Abstract: An established treatment strategy in surgical site infection after hindfoot and ankle surgery is a two-stage procedure with debridement and placement of a cement spacer, followed by antibiotic treatment and secondary arthrodesis. However, there is little evidence to favor this treatment over a one-stage procedure with debridement, followed by primary arthrodesis with an Ilizarov external fixator and antibiotic treatment. We compared the infection control and clinical and radiological outcome of a two-stage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“… 8 They reported that infection after hindfoot surgery was a significant problem and could result in significant complications that may require revision surgeries, including amputation. 12 , 14 Saibaba and Gopinathan 25 reported that limited vascularity combined with the force going through the hindfoot including calcaneus could predispose it to infection. However, there is no consensus for why hindfoot surgery is more risky in postoperative infection compared with the forefoot/midfoot surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 8 They reported that infection after hindfoot surgery was a significant problem and could result in significant complications that may require revision surgeries, including amputation. 12 , 14 Saibaba and Gopinathan 25 reported that limited vascularity combined with the force going through the hindfoot including calcaneus could predispose it to infection. However, there is no consensus for why hindfoot surgery is more risky in postoperative infection compared with the forefoot/midfoot surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ankle arthrodesis combined with radical debridement may be the most suitable option to eradicate an infection and salvage the limb [12,19,21,22,27,34,37,39]. Although numerous fusion methods have been proposed, there is controversy about the most effective technique [9,21,26,27,34]. To explore whether ankle arthrodesis using an Ilizarov external fixator is an effective treatment for septic ankle arthritis, we assessed the fusion rate, complications, reoperations, and patient-reported outcome measures of patients in our study after a minimum of 6 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In most patients-more than 90%-treated with an Ilizarov external fixator for ankle arthrodesis to treat septic ankle arthritis, osseous fusion was achieved by 12 months. Few studies we know of have described ankle arthrodesis in patients with septic ankle arthritis, and the fusion rate ranged from 61% to 100% in previous studies [4,9,12,19,21,22,27,33,34,37,39]. Good soft tissue condition, eradication of infection, and rigid fixation are key factors to achieve bony fusion [12,21,39].…”
Section: Percentage Of Patients Who Achieved Bony Fusionmentioning
confidence: 99%
See 2 more Smart Citations